Assessment of Quality of Sexual Life in Male Patients with Psoriasis - Uddin, Md Rokon (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 216